Study on problems in forensic DNA identification standardization in China and countermeasures for the same - Li Yuan (Wolters Kluwer Medknow Publications, 2018)
Forensic DNA analysis plays an important role in criminal cases, civil cases, missing persons' identification, and other truth-ascertaining activities. Selection of an appropriate laboratory for DNA testing, use of amplification reagents, management of database and other standardized operations, standardization of system for biological evidence in terms of sample collection, and sample analysis will improve the quality and credibility of the identification work. However, current forensic DNA standardization in China encounters some problems with respect to the development of standard and technical specification, standard documents, and DNA evidence review and acceptance. Thus, introduction and refinement of the standardization system require collective knowledge and continuous efforts. Moreover, standardization could not replace court review, and expert reports still should be cross-examined in courts.